Sleep-EEG-based parameters for discriminating fatigue and sleepiness - Fujiwara, Koichi; Goto, Yuki; Sumi, Yukiyoshi; Kano, Manabu; Kadotani, Hiroshi (Frontiers in Sleep, 2022)
Sleep quality can be evaluated from the viewpoint of recovery from fatigue and sleepiness; however, it is difficult to investigate sleep quality while distinguishing between the two. The aim of this study is to find biomarkers that can discriminate between daytime fatigue and sleepiness and to assess sleep quality in consideration thereof. We collected answers to questionnaires regarding daytime fatigue and sleepiness, as well as EEG data measured during sleep, from 672 city government employees in a rural area of Japan. The respondents were categorized into four groups in accordance with the severity of fatigue and sleepiness as assessed by the questionnaires: fatigued and sleepy (FS), fatigued, non-sleepy (FO), non-fatigued and sleepy (SO), and non-fatigued and non-sleepy (neither fatigued nor sleepy; NE) groups. EEG data of medial frontal electrodes were obtained with a one-channel portable electroencephalograph, and various sleep parameters such as powers or sleep durations in each stage were compared among the four groups. Statistical tests confirmed significant differences in some derived sleep parameters among the four groups. The Theta Delta power may be a biomarker that can discriminate between fatigue and sleepiness. In addition, the Delta and Theta powers may be associated with sleep quality in terms of recovery from sleepiness and fatigue, respectively. Moreover, high frequency or long duration of mid-arousals may contribute to recovery from fatigue. The results showed that fatigue and sleepiness have different effects on sleep, and multiple sleep parameters derived from EEG are associated with sleep quality.